Pengaruh Financial Literacy, Uang Elektronik, Demografi, Gaya Hidup dan Kontrol Diri terhadap Perilaku Konsumtif Generasi Milenial Di Kota Surabaya - Priscilla Irene Sudiro; Nadia Asandimitra (Jurnal Ilmu Manajemen, 2022)
One of the fundamental things in human life as an economic creature is to fulfil their needs. Humans are also equipped with the knowledge and high self-control about their lifestyle, or else they can trigger a consumptive attitude. The research objective is to analyze the influence of financial literacy, electronic money, demographics, lifestyle, and self-control on consumptive behaviour. This research investigates the millennials in Surabaya and data collection techniques using purposive and snowballs sampling. Around 284 millennial generations in Surabaya have chosen to be the respondents in this research. They fill out an online questionnaire using the Structural Equation Modeling (SEM) analysis technique with AMOS software version 24. The study proves that financial literacy, electronic money, demographics, lifestyle, and self-control significantly affect consumption. This research expects to awaken various parties, especially about the importance of knowledge in financial management, to form high self-control to decide a rational consumption activity for the millennial generation.